Homonymy Analysis in Taylor Swift’s Songs - Dian Noviani Syafar; Herfyna Asty (Fakultas Sastra Universitas Ekasakti, 2022)
This research aims to determine the types of ambiguous words and the meanings of ambiguous words in Taylor Swift's songs. The researcher uses Ullmann's theory to determine the type of ambiguous word. The research design is a qualitative research. The research instrument is the researcher himself. The data sources for this study are the audio and lyrics of Taylor Swift's songs The data of this study are ambiguous words contained in Taylor Swift's songs. In collecting the data, the researcher applies the non-participant observation method and the note taking technique as a follow-up technique. Data analysis conducts the referential method with the language references as the determinant. The researcher finds out homonyms in the songs whose meanings were not related and the actual meanings matched the context in the song lyrics. This research also focuses on homograph and homophone.